1978
DOI: 10.1007/bf01477293
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the activity of the renin-angiotensin-aldosterone system (RAAS) in patients with cirrhosis of the liver

Abstract: Plasma renin activity (PRA), plasma renin concentration (PRC), angiotensinogen, angiotensin II (AT II) and plasma aldosterone were determined by radioimmunoassay in 77 patients with cirrhosis of the liver [group I: with ascites, untreated (n=23); group II: patients with ascites during treatment (n=32); group III: after removal of fluids, but under further spironolactone therapy (n=10); group IV: untreated subjects without ascites (n=12)]. With the exception of decreased angiotensinogen values in all groups ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
2

Year Published

1983
1983
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 53 publications
4
26
2
Order By: Relevance
“…Moreover, we have been able to confirm the direct relationship between portal venous pressure on one side and PRC and ALD on the other side, as first described by Bosch et al in 1980." This indicates to us that most often RAAS is activated during decompensation, suggesting an underfilling of the central vascular bed with activated volume and barorece~tors.…”
Section: Renin-angiotensin-aldosterone Systemsupporting
confidence: 77%
“…Moreover, we have been able to confirm the direct relationship between portal venous pressure on one side and PRC and ALD on the other side, as first described by Bosch et al in 1980." This indicates to us that most often RAAS is activated during decompensation, suggesting an underfilling of the central vascular bed with activated volume and barorece~tors.…”
Section: Renin-angiotensin-aldosterone Systemsupporting
confidence: 77%
“…On the whole, urinary sodium excretion in these patients was significantly correlated with GFR values. It has been shown that about 40% of patients with "early" ascites have normal PRA and aldosterone plasma levels (43)(44)(45); we observed that 3 of 10 ascitic patients had PRA and aldosterone values within the normal range (data not shown).…”
Section: Discussioncontrasting
confidence: 63%
“…In our patients with liver cirrhosis, baseline urinary excretion of free aldosterone was not significantly higher in contrast to the previous observations [ 13]. In this con text, Bernardi et al [14] recently demonstrated that renin and plasma aldosterone were not elevated in cir rhotic patients.…”
Section: Discussioncontrasting
confidence: 55%